Pesticide residues in beebread and honey in Apis cerana cerana and their hazards to honey bees and human - Feiran Wang; Yuhao Wang; Yong Li; Shiwen Zhang; Pengzhen Shi; Hongmei Li-Byarlay; Shudong Luo (Ecotoxicology and Environmental Safety, 2022)
The residue of pesticides in bee products such as beebread and honey threaten the survival of pollinators and human health. Apis cerana cerana is one of the leading managed honey bees in China. However, little is known about the residues of pesticides in hive products of A. c. cerana in China. Here, we investigated the pesticide residues in beebread and honey. The risk of detected residues of pesticides to honey bees was evaluated with hazard quotient (HQ) and BeeREX. Furthermore, we assessed the chronic and acute risks to humans according to the dietary exposure. Our results suggest that the pesticide residues detection ratio (25.4% for beebread and 2.8% for honey) and the concentrations of these residues is lower than previously reported. Additional risk assessments indicate that the residue levels of pesticides in tested honey of A. c. cerana do not pose a risk for human consumers. Among all identified pesticides, only thiamethoxam raises the concern for further risk assessment in the risk evaluation of honey bee colonies and thiamethoxam was safe for colonies in higer tier studies